2021
DOI: 10.1177/0049475520979298
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiogram of non-fermenting Gram-negative bacilli in blood stream infections: Study in a tertiary care centre, Western Uttar Pradesh, India

Abstract: Non-fermenting Gram-negative bacilli (NFGNB) are emerging as important cause of blood stream infections. We aimed to determine the prevalence and antibiotic susceptibility pattern of NFGNB isolated from blood of patients with sepsis. We found, in 176 patients, the most common to be Pseudomonas aeruginosa (74) and Acinetobacter baumanii complex (39) followed by Stenotrophomonas maltophilia (16), Sphingomonas paucimobilis (6), Burkholderia cepacia (5) and Ochrobactrum anthropic (1). Generally, organisms showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…Varied isolation rates were recorded in different studies. The results of our study were parallel with those conducted by Nazir et al, Sarwat et al, Juyal et al, Grewal et al, Manjunath et al, and Chang and Huang, who have reported a positivity rate of 9.3%, 11.2%, 11.6%, 16.9%, 28.3%, and 31.62%, respectively, in their studies [ 1 , 4 , 7 , 8 - 10 ]. Malini et al, in their study, reported a 4.5% isolation rate [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Varied isolation rates were recorded in different studies. The results of our study were parallel with those conducted by Nazir et al, Sarwat et al, Juyal et al, Grewal et al, Manjunath et al, and Chang and Huang, who have reported a positivity rate of 9.3%, 11.2%, 11.6%, 16.9%, 28.3%, and 31.62%, respectively, in their studies [ 1 , 4 , 7 , 8 - 10 ]. Malini et al, in their study, reported a 4.5% isolation rate [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…The correct and rapid identification of such bacteria in a clinical microbiology lab, along with antimicrobial susceptibility testing, is an essential step toward the effective treatment of septicemic patients. BSIs caused by NFGNB pose a challenge for clinicians and microbiologists because the laboratories have limited facilities for their identification and emerging antimicrobial resistance [ 4 ]. An increase in resistance to antimicrobials is common among NFGNB; few strains are resistant to commonly used antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood and LRT specimens had comparable frequencies of NFGNB (4). An Indian teaching hospital reported 10% of clinical isolates to be NFGNB, while in another report, 16.9% of all pathogens from BSIs were NFGNB [17 ▪ ,18]. In a Chinese multicentre laboratory-based study of paediatric blood stream pathogens, P. aeruginosa and S. maltophilia were positioned among the top 10 pathogens, 6th and 8th, respectively [19].…”
Section: Text Of Reviewmentioning
confidence: 98%
“…It is noteworthy that Elizabethkingia spp. and S. maltophilia , due to the intrinsic resistance, are associated with infections after prolonged carbapenem therapy [18,49 ▪▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%